Trade and Industrial Policies with Heterogeneous Firms: The Role of Country Asymmetries - Michael Pflüger; Stephan Russek (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2011)
This paper explores the role of country asymmetries for trade and industrial policies with heterogeneous firms. Our analysis delivers a number of novel results. First, trade policies, infrastructure policies and industrial policies which improve the business conditions in one country have negative productivity and welfare effects on the trading partner. Second, symmetric trade liberalization is immiserizing for a trading partner whose business conditions are inferior. Third, there are gains from trade even for a country whose monopolistically competitive sector with heterogeneous firms is wiped out by the switch from autarky to trade.
Keywords: F12; F13; F15; L25; 330; firm heterogeneity; welfare; trade policies; industrial policies; business conditions; Außenwirtschaftspolitik; Industriepolitik; Standortpolitik; Mehr-Länder-Modell; Produktivität; Wohlfahrtsanalyse; Außenhandelsliberalisierung; Außenhandelseffekt; Theorie